ANALISIS PERTUMBUHAN DAN LAJU EKSPLOITASI IKAN TONGKOL (Auxis thazard) YANG DIDARATKAN DI KUD GABION PELABUHAN PERIKANAN SAMUDERA BELAWAN SUMATERA UTARA - Kartika Dewi; Ternala Alexander Barus; Desrita Desrita (Program Studi Manajemen Sumberdaya Perairan, Fakultas Pertanian Universitas Sumatera Utara, 2015)
Tuna fish (Auxis thazard) has high economic value in Medan. This research was conducted to investigate the impact of exploitation on Tuna fish stock and was from November 2014 to April 2015. Data obtained in KUD location Gabion Belawan. The objective of this research is to study stock condition of Tuna fish based on length-weight relationship, Von-Bertalanffy growth parameter, condition factor, mortality and level of exploitation. Total length data was measured from 555 fish the average of total length was from 183-402 mm. Separation of cohort length groups using Bhattacharya method produced four length frequency. Growth coefficient (K) was 0.38 per year, L infinity (L∞) 411.60 mm and t0 – 1.42 per year. Based on the long relationship expressed heavy growth patterns swordfish in the waters of the Strait of Malacca is alometrik negative, the value of the average condition factor 0,51 – 2,59, it showed the fish in suitable circumstances. Total mortality rate (Z) is 1,95 per year, natural mortality (M) 0,43 per year, and the rate of cacth mortality (F) 1,46 per year to obtain the exploitation rate of 0,74. The exploitation rate value has exceeded the optimum value of 0,5Keywords : Auxis thazard, Growth, Mortality, Malacca Strait